Total Ankle Arthroplasty with Simultaneous Versus Secondary Hindfoot Arthrodesis. Issue 3 (14th September 2018) - Taylor, Michel; Cody, Elizabeth; Easley, Mark; Parekh, Selene; Nunley, James; Adams, Samuel
Category: Ankle Arthritis Introduction/Purpose: Total ankle arthroplasty (TAA) for ankle arthritis leads to a more normal gait pattern compared to ankle arthrodesis, prompting many to hypothesize that TAA slows development of adjacent joint arthrosis. However, following TAA, patients may also develop hindfoot pain, deformity and dysfunction, ultimately requiring arthrodesis procedures. Many patients with AA also have subtalar and/or talonavicular arthrosis. In these cases, simultaneous TAA and hindfoot arthrodesis may be performed. Previous studies have found that TAA in conjunction with hindfoot arthrodesis procedures led to inferior outcomes compared to isolated TAA. The purpose of this analysis was to compare the functional outcomes of simultaneous vs. subsequent hindfoot arthrodesis procedures and to describe the change, if any, in outcome scores following a subsequent hindfoot arthrodesis procedure. Methods: After receiving Institutional Review Board approval, the TAA database at our institution was reviewed for all TAA performed between 1998 and 2015. All patients who received a TAA and either a simultaneous or subsequent hindfoot arthrodesis with at least two years of clinical follow up were included in the analysis. All surgeries were performed by one of three fellowship-trained orthopaedic foot and ankle surgeons with extensive experience in TAA and associated hindfoot arthrodesis procedures. Outcome measures included preoperative and 2-year postoperative visual analog scale (VAS) scores, Short Musculoskeletal Function Assessment (SMFA), Short Form (SF)-36 and American Orthopaedic Foot and Ankle Society (AOFAS) Ankle-Hindfoot scores. Results: 64 patients met the inclusion criteria. 39 patients underwent TAA with simultaneous hindfoot arthrodesis (Sim) and 25 underwent a subsequent arthrodesis procedure (Sub) an average 22.2 months following TAA. 20 patients underwent double arthrodesis (11 Sub) and 44 patients underwent subtalar fusion (14 Sub). There were no differences in preoperative questionnaire scores between the two groups. Both the Sim and Sub groups experienced significant improvement in their postoperative VAS, SMFA, SF-36 and AOFAS scores. Postoperative VAS and SMFA bother scores were significantly lower for the Sim group (p<0.05). In the Sub group, there was no difference in outcome scores before and after the fusion procedure. Demographics and questionnaire scores are shown in the Table. Conclusion: These results support previous findings demonstrating significant functional improvement and decrease in pain scores following TAA and associated fusion procedures. However, these results also suggest that simultaneous fusion procedures may provide better reduction in pain when compared to sequential procedures. In addition, for patients who underwent subsequent fusion, the improvement experienced in terms of pain and function tends to be maintained postoperatively.